MANAJEMEN DIRI PELAJAR SUKSES DI MASA DEPAN DI SMK MUHAMMADIYAH 3 KLATEN UTARA - Ambar Winarti; Agus Murtana; Mawardi, Mawardi (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Strengthening self-management is an essential component in shaping students' character and readiness to face future life challenges, both in the workforce and in higher education. This community service program aimed to enhance the understanding and self-management skills of 12th-grade students at SMK Muhammadiyah 3 Klaten Utara through structured education and training. The methods employed included interactive lectures, group discussions, and decision-making simulations covering aspects such as time management, discipline, intrinsic motivation, and life goal planning. The results indicated a significant increase in students’ awareness of the importance of self-management in supporting both academic and non-academic success. Student responses demonstrated high enthusiasm, with more than 85% of participants stating that the materials provided were relevant and applicable to their lives. This community engagement initiative is expected to serve as a sustainable intervention model in character education and soft skills development among vocational students, particularly in the Klaten region and its surroundings